2006
DOI: 10.1111/j.1474-919x.2006.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Information needs to support environmental impact assessment of the effects of European marine offshore wind farms on birds

Abstract: European legislation requires Strategic Environmental Assessments (SEAs) of national offshore wind farm (OWF) programmes and Environmental Impact Assessments (EIAs) for individual projects likely to affect birds. SEAs require extensive mapping of waterbird densities to define breeding and feeding areas of importance and sensitivity. Use of extensive large scale weather, military, and air traffic control surveillance radar is recommended, to define areas, routes and behaviour of migrating birds, and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 23 publications
(37 reference statements)
0
100
1
4
Order By: Relevance
“…Where their demographic rates are governed by density-dependence, it is more likely that the population can replace lost individuals. Long-lived species, which raise few young during the course of their lifetime, may thus be particularly sensitive to MREI impacts on mortality and reproduction (Fox et al, 2006). As populationlevel impacts also depend on population size, species with small populations may also be particularly vulnerable.…”
Section: Population-level Impactsmentioning
confidence: 99%
“…Where their demographic rates are governed by density-dependence, it is more likely that the population can replace lost individuals. Long-lived species, which raise few young during the course of their lifetime, may thus be particularly sensitive to MREI impacts on mortality and reproduction (Fox et al, 2006). As populationlevel impacts also depend on population size, species with small populations may also be particularly vulnerable.…”
Section: Population-level Impactsmentioning
confidence: 99%
“…Indeed, there are probably more publications on how to assess these impacts than there are empirical studies (e.g. Fox et al 2006). The field is thus unusual in that the theoretical aspects (i.e.…”
Section: Offshore Construction (Wind Farms Oil and Gas Extraction)mentioning
confidence: 99%
“…As there are limited data available on the collision mortality of seabirds with offshore wind farm structures [46], caution should be taken in drawing general conclusions. The further development of radar and thermal imaging hardware and associated software is therefore required to gather data on actual collision rates for a range of species.…”
Section: Sea Birdsmentioning
confidence: 99%
“…Such avoidance behaviour may have several consequences, one of which is an increase in the energy demands of an individual bird, because of increased distances flown in order to avoid a wind farm. The impact of extended or modified flight lengths due to the presence of a wind farm site may be small in energetic terms for migratory birds [48] but could have greater consequences for wintering birds commuting daily between feeding and roosting areas e.g., common eider and common scoter Melanitta nigra [46,48]. A study at the Nysted offshore wind farm reported an added distance of c.500 m to migratory common eider as the consequence of the wind farm's presence in their migratory flight path.…”
Section: Sea Birdsmentioning
confidence: 99%
See 1 more Smart Citation